DESAIN LOADING DOCK DAN PENENTUAN LEVEL STOCK UNTUK MEREDUKSI JUMLAH ANTRIAN DAN PERSEDIAAN PADA AREA PENERIMAAN BARANG (Studi Kasus : Perusahaan Otomotif Internasional)) - Haryo Santosa; Sri Hartini; Meilisa Karima R (TEKNIK, 2010)
Loading docks must be located for easy access by service vehicles and should be separate from public entrancesto the building, public spaces, and other light industrial or warehouse zones. However, it is also important thatthey are designed to ensure the safety and security of their users and the users of other nearby spaces. Thisresearch would be tryied to design the schedule of arrival time and cycle issue in the part preparation. To reducemaximum inventory, this research have been determinated level stock. Its result that the number of queue canreduce from 5 to 2 in each line and maximum inventory can reduce 49%